2017
DOI: 10.5815/ijmecs.2017.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction Activities Identification in Software Component Integration for Component Based Software Development (CBSD)

Abstract: Abstract-In the modern era, the ideas related to software developments are totally replaced the old traditional software development to CBSD. CBSD is the approach that can provide reusability of components to develop new software under minimum chances of risks. Beyond the CBSD features, there are still some significant risks overall the development phase. Generally, the quality of a developed software is depending upon the component integration phase. Nevertheless, component integration phase plays a tremendou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The intelligent ant agents optimize their routes and activities to minimize energy consumption while maintaining effective intrusion detection. The decentralized nature of SAZIDS enhances its scalability and resilience [23]. Ant agents operate autonomously, contributing to the robustness of the intrusion detection system.…”
Section: Related Workmentioning
confidence: 99%
“…The intelligent ant agents optimize their routes and activities to minimize energy consumption while maintaining effective intrusion detection. The decentralized nature of SAZIDS enhances its scalability and resilience [23]. Ant agents operate autonomously, contributing to the robustness of the intrusion detection system.…”
Section: Related Workmentioning
confidence: 99%
“…In figure 3 we have discussed the basic threats of cloud computing. We have discussed technological, human-related and hardware, and software-based threats in this taxonomy diagram [41]. [4] discussed that, due to the progress of web innovation, the content of data is becoming quite gigantic.…”
Section: Cloud Computing Threatsmentioning
confidence: 99%
“…They identified the key distinguishing factors of software components that need to be addressed to ensure successful integration, such as component behavior and a logical execution environment. Fatima et al [8] conducted a semi-systematic survey to identify risk factors for the integration of software components. They concluded that a lack of interoperability standards, glue code, and format variation are the key reasons for failure to integrate.…”
Section: Related Workmentioning
confidence: 99%